Pemahaman Lembaga Penyiaran Radio di Provinsi Sumatera Barat dalam Pemenuhan Kebutuhan Informasi Khalayak - Ardian Ardian (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2018)
This article describes about the analysis of  the understanding of institutions of broadcasting radios in west sumatera to fulfill the need of social information. This research is based from the phenomenon in the field showing the decrease of social interest in listening to a radio closed by the modernization of mass communication.  To reveal the reality in the field, this research used constructive paradigm, qualitative methods and case study approach. The research data was collected by interviewing 5 key informen and documentation study. Based on the result of analysis in the field in completing the need of social information, the researcher concluded as followed: (1) Radios in West Sumatera comprehend the 3 functions of communication in fulfilling social information needs: (a) information, (b) social learning, and (c) entertainment. That was seen from the constructions of the broadcasting programs produced; (2) In the effort of fulfilling the need of information, radios conduct surveys, observations and researches of the market that need information; and (3) Radio broadcasting board of West Sumatera comprehends that in information dissemination KPID of West Sumatera is the regulator taking roll in supervising the broadcasting programs and any kinds of violations than by the radios.